Development of a human papillomavirus type 6/11 vaccine candidate for the prevention of condyloma acuminatum. Issue 32 (6th August 2018) - Yu, Yue; Guo, Jianfeng; Li, Dingfeng; Liu, Yong; Yu, Yongli; Wang, Liying
Highlights: Development of a specific prophylactic HPV6/11 vaccine for condyloma acuminatum. The HPV6/11 vaccine provides a good choice for prevention of CA in males. The HPV 6/11 L1 VLPs were produced in Hansenula polymorpha with correct structure. The HPV6/11 vaccine shows high immunogenicity in both mice and cynomolgus monkeys. Abstract: Condyloma acuminatum (CA) represents a significant human papillomavirus (HPV) disease burden worldwide, resulting in substantial healthcare costs and loss of life quality in both genders. To address this problem, we tried to develop a bivalent HPV6/11 virus-like particle (VLP) vaccine targeting CA. HPV6/11 VLPs were generated in Hansenula polymorpha, and a disassembly and reassembly (D/R) treatment was further conducted to improve the stability and monodispersity of the VLPs. The HPV6/11 VLPs were identified by transmission electron microscopy (TEM), high performance liquid chromatography (HPLC), mass spectrum (MS) and dynamic light scattering (DLS), and were evaluated for their immunogenicity in both mice and cynomolgus monkeys. The results showed that the HPV6/11 L1 proteins were correctly expressed and assembled into HPV6/11 VLPs, and the HPV6/11 VLPs formulated with aluminum phosphate induced vigorous production of specific neutralizing antibodies against HPV6/11 VLPs in mice and cynomolgus monkeys. These data indicated that the Hansenula polymorpha -derived HPV6/11 VLPs could be formulated into a bivalent vaccine used in prevention of CA.